HUBUNGAN POSISI MENYUSUI, KELAINAN PUTING SUSU, PERAWATAN PAYUDARA TERHADAP TERJADINYA BENDUNGAN ASI DI RUMAH SAKIT UMUM DAERAH BANYUASIN - Hartati, Depi (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2019)
Breast milk dam is a dam that occurs in the breast glands due to the expansion and pressure of milk production and storage. In Indonesia, the most common problem in breastfeeding is blistered nipples. About 57% of breastfeeding mothers have had nipple blisters. This is due to errors in breastfeeding techniques. Chafed nipples caused by errors in breastfeeding techniques, namely the baby does not feed until the areola of the mother so that the baby's gums do not press on the mother, pain / blisters will occur on the nipples. This study aims to determine the relationship between breastfeeding position, nipple disorders, and breast care with breast milk shading. This research is cross sectional using primary data. The population of all postpartum mothers who visited the MCH clinic during the study and the sample amounted to 47 respondents who were taken using the accidental sampling technique. The results were obtained from 47 respondents, 23 respondents (48.9%) experienced breast milk damages, 27 respondents (57.4%) who had nipple abnormalities, 29 (61.7%), had the wrong breastfeeding position. and those who do breast care are 23 respondents (48.9%). In the bivariate analysis, it was found that breastfeeding position (Pvalue = 0.011), nipple disorders (Pvalue = 0.010) and breast care (Pvalue = 0.013) had a significant relationship with the occurrence of breast milk damages. This research is expected to add insight and knowledge and can increase information and health promotion related to breast milk dams.